Coral Database and Monitoring System Design for Ecological Sustainability - Singgalen, Yerik Afrianto (Journal of Information System and Informatics, 2024)
Several factors contribute to the importance of designing a coral monitoring system. Firstly, coral reefs are ecologically crucial ecosystems, providing habitat for numerous marine species and supporting biodiversity. Therefore, monitoring coral reefs is essential for understanding population dynamics and ecosystem health. Secondly, coral reefs are vulnerable to climate change, pollution, overfishing, and human activities. With a monitoring system, we can identify factors damaging coral reefs and take necessary prevention or restoration actions. Thirdly, coral reef monitoring aids in informing policies and sustainable resource management. By comprehensively understanding coral reef conditions, we can develop more effective management strategies to protect and preserve these ecosystems for future generations. This research aims to design a coral monitoring system to identify factors contributing to coral reef degradation. The method employed is Rapid Application Development (RAD), with stages including requirement planning, user design, construction, and cutover. The findings of this study indicate that the application can meet user needs. The findings of this research emphasize the urgent need for the development and implementation of coral monitoring applications as a strategic step toward reducing environmental degradation for ecological sustainability. The research underscores the critical role of monitoring tools in assessing and mitigating the impacts of human activities and environmental stressors on coral reef ecosystems through comprehensive data analysis and evaluation. This highlights the importance of proactive measures to address the increasing threats facing coral reefs and emphasizes the significance of technological innovations in facilitating practical conservation efforts.